The Relationship of Religiosity with Students' Critical Thinking Skills on the Subject of Stoichiometry - Shavira Aini Az-Zahra; Ayi Darmana (Jurnal Inovasi Pembelajaran Kimia (Journal of Innovation in Chemistry Education), 2023)
Education is a learning process that is important for human life in producing quality humans. In studying science, religious science is needed to maintain balance in order to give birth to good habits in the activities of each individual. Science and religion are two things that reinforce each other. Science is present is expected to provide evidence so that it will improve the quality of one's beliefs. Similarly, the presence of religion in science can make science more useful and increase its benefit. This study aims to see the relationship between religiosity and students' critical thinking skills in class XI IPA SMA Negeri 3 Binjai. The method used is an analytical method using the Pearson correlation test. The subjects in this study were grade XI students of SMA Negeri 3 Binjai which amounted to 107 students. The instrument used was a religiosity questionnaire with 15 statements and Using critical thinking skills questions on stoichiometry material totaling 18 questions. The results of the study found that the average level of students' critical thinking skills on stoichiometric material was 29.71 and the average level of student religiosity was 42.94. The correlation coefficient between religiosity and critical thinking skills obtained is 0.809 which means that there is a strong relationship between religiosity and critical thinking skills of students in class XI IPA SMA Negeri 3 Binjai.